2006
DOI: 10.1007/s10517-006-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and LPS-induced secretion of cytokines by villous chorion tissue

Abstract: Secretion of IL-1alpha, IL-1beta, IL-6, IL-10, and TNF-alpha cytokines by villous chorion cultures (7-14 weeks) during normal pregnancy and in spontaneous abortions was studied. Secretion of IL-1alpha and IL-6 increased 4.5 and 7.3 times in miscarriages, while secretion of IL-1beta, IL-10, and TNF-alpha decreased. LPS stimulated the production of IL-1alpha and IL-6 in samples obtained during surgical abortion. LPS stimulated IL-1alpha and TNF-alpha secretion in miscarriages, while the level of IL-6 production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Additionally, low-grade inflammation in the placenta, as observed with low doses of HSV-2 in our study, has been observed in pregnancies complicated by maternal obesity that result in adverse pregnancy outcomes, including congenital abnormalities and fetal macrosomia, in the absence of more severe outcomes [63,64]. Further, in a study conducted using first trimester placental tissues obtained from normal pregnancies and spontaneous abortions, only placental tissues from spontaneous abortions were associated with unstimulated production of inflammatory mediators [65]. This may point to a role of other placental factors in enhancing pro-inflammatory cytokine production, which underlies severe placental pathology and fetal death, as observed following high-dose infection in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, low-grade inflammation in the placenta, as observed with low doses of HSV-2 in our study, has been observed in pregnancies complicated by maternal obesity that result in adverse pregnancy outcomes, including congenital abnormalities and fetal macrosomia, in the absence of more severe outcomes [63,64]. Further, in a study conducted using first trimester placental tissues obtained from normal pregnancies and spontaneous abortions, only placental tissues from spontaneous abortions were associated with unstimulated production of inflammatory mediators [65]. This may point to a role of other placental factors in enhancing pro-inflammatory cytokine production, which underlies severe placental pathology and fetal death, as observed following high-dose infection in our study.…”
Section: Discussionsupporting
confidence: 58%
“…In mouse pregnancy, preterm birth tended to be characterized by increased levels of several proinflammatory factors, while there was a downregulation of Il-10 [73]. Likewise in chorionic villous cultures from early miscarriages, Il-10 was attenuated while IL-1a and Il-6 were elevated [74]. In the presence of intra-amniotic infection at term, there was a higher level of amniotic fluid Il-10 than among term pregnancies without infection, and in both term and preterm birth, the Il-10 was elevated [75] which on the surface seems counterintuitive but may reflect a feedback mechanism to dampen the proinflammatory reaction after parturition.…”
Section: Cervical Inflammatory Reactions and Preterm Birthmentioning
confidence: 99%
“…[4][5][6] Cytokines are pleiotropic polypeptides involved in the modulation of immune responses and inflammatory reactions which take place at the feto-maternal interface in both normal and abnormal pregnancy. [9][10][11] Previous studies have measured the partial pressure of oxygen (O 2 ) within the human placenta in vivo. 8 There is evidence for a shift in Th1 (TNFα): Th2 (IL-10) ratio in early pregnancy loss in the maternal circulation and placenta.…”
Section: Introductionmentioning
confidence: 99%
“…8 There is evidence for a shift in Th1 (TNFα): Th2 (IL-10) ratio in early pregnancy loss in the maternal circulation and placenta. [9][10][11] Previous studies have measured the partial pressure of oxygen (O 2 ) within the human placenta in vivo. During early first trimester, there is physiologically low O 2 (<10%) as opposed to ambient O 2 tension of 21%.…”
Section: Introductionmentioning
confidence: 99%